Penerapan Gerakan Budaya Literasi Bahasa Indonesia SD Negeri 055981 Beruam - Priska Nurlia Br Simanungkalit; Novi Astika Rambe; Wisman Hadi; Elly Prihasti Wuriyani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to describe the application and constraints in the Indonesian literacy culture of SD Negeri 055981 Beruam. This study uses a qualitative approach with the method of literature study and observation and the results of the study explain in its application there are three phases namely familiarizing, developing and teaching. When this Indonesian literacy culture is implemented, there are obstacles faced and the obstacles come from within and outside such as the level of student readiness, supporting facilities, society and government.